INOVASI EFEKTIF: UPAYA MEMPERTAHANKAN DAN MENANGKAP PASAR POTENSIAL - Hendrayanti, Endang (Fakultas Ekonomi Universitas Islam 45, 2011)
Globalization has become an unavoidable phenomenon in a business world, the world economy is now more open, and the service and goods traffics have already gone through the countries* borderlines. Organizations/companies which can survive must have a very strong competitiveness such as the good human resources, the good technology, good capital, and good innovation. Yet, the creative innovation with a qualified product and suitable to market need will survive, therefore, the success key of the company is, always owns the high creativity, Innovation, marketing ability and technology to survive in the global market